PENGARUH PENGGUNAAN MEDIA POWERPOINT TERHADAP MINAT DAN HASIL BELAJAR SISWA SDN BAREBELIK - AKHMAD JAMILUDIN; ERLAN HARTAWAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Learning media has a considerable influence in the learning process. knowing the effect of using Powerpoint media on interest in learning and student learning outcomes in science learning. This type of research is a quantitative research design with a Quasi-experiment design: One-Group Pre-test-Post-test Design with one type of treatment. The research design used Pre-test-Post-test Design. The subjects of this study were all grade IV B students of SD Negeri Barebelik in the 2021/2022 academic year. The data obtained consisted of data on interest in learning scores and scores of science learning outcomes for experimental group students. The instrument used is a learning interest questionnaire and a science learning outcome test. The data were analyzed to determine the effect of Powerpoint media on students' interest in learning and student learning outcomes based on pre-test and post-test in the experimental group. Interest in learning science in grade IV SD Negeri Barebelik increased by 67.65%, namely from the result of the difference in the percentage before learning and after learning. Meanwhile, the science learning outcomes of the fourth grade students of SD Negeri Barebelik increased by 52.94% from the difference in the percentage before and after learning. There is an influence of Power-point media on learning interest and science learning outcomes for class IVB students at SD Negeri Barebelik in the 2021/2022 academic year. ABSTRAKMedia pembelajaran memiliki pengaruh yang cukup besar dalam proses pembelajaran. mengetahui pengaruh penggunaan media Powerpoint terhadap minat belajar dan hasil belajar siswa pada pembelajaran IPA. Jenis penelitian ini adalah penelitian kuantitatif dengan desain penelitian Quasi-experiment design: One-GroupPre-test-Post-test Design dengan satu macam perlakuan. Rancangan penelitian menggunakan Pre-test-Post-test Design. . Subjek penelitian ini adalah semua siswa kelas IV B SD Negeri Barebelik Tahun Ajaran 2021/2022. Data yang diperoleh terdiri atas data skor minat belajar dan skor hasil belajar IPA siswa kelompok eksperimen. Instrumen yang digunakan adalah angket minat belajar dan tes hasil belajar IPA. Data dianalisis untuk mengetahui pengaruh media Powerpoint terhadap minat belajar siswa dan hasil belajar siswa berdasarkan pre-test dan post-test pada kelompok eksperimen. Minat belajar IPA siswa kelas IV SD Negeri Barebelik meningkat 67,65% yaitu dari hasil selisih persentase sebelum pembelajaran dan sesudah pembelajaran. Sedangkan, Hasil belajar IPA siswa kelas IV SD Negeri Barebelik meningkat 52,94% dari selisih persentase sebelum dan sesudah pembelajaran. Terdapat pengaruh media Power-point terhadap minat belajar dan hasil belajar IPA siswa kelas IVB SD Negeri Barebelik Tahun Pelajaran 2021/2022.